Method for producing hvlp ultra-low profile copper foil for 6g communication and computing power mainboard
Patent Information
- Application Number
- CN202611144362.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-09
AI Technical Summary
现有技术往往只能采取折中方案,无法同时获得超低粗糙度和优良的力学性能
1)破解了“粗糙度-强度”技术矛盾:通过缓蚀剂差异化吸附和梯度温度协同,首次实现了工业级的“选择性整平”,将Rz降至0.5μm以下的同时基体几乎不减薄,颠覆了现有技术中“要整平必减薄”的技术偏见;
Smart Images

Figure CN122879709A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolytic copper foil deep processing and manufacturing technology, specifically relating to a method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards. Background Technology
[0002] In scenarios such as 5G / 6G high-frequency communication and AI computing, the skin effect in signal transmission makes the surface microstructure of copper foil a key factor determining insertion loss. Excessive surface roughness drastically increases transmission attenuation and crosstalk of high-frequency signals. Furthermore, the rough surface creates micropores at the interface with resin during lamination, which can easily lead to delamination and blistering during high-temperature processes such as reflow soldering, resulting in circuit board failure. Therefore, the industry urgently needs ultra-low profile (HVLP) copper foil with a surface roughness Rz of less than 0.5 μm.
[0003] Existing ultra-low profile copper foil production technologies are mainly divided into two categories: one is to directly obtain a low roughness surface by adjusting the electrolytic parameters of the green foil, but the process window is extremely narrow, making it difficult to balance peel strength and stable mass production; the other is to perform post-processing and leveling on conventional green foil, among which chemical etching leveling is the main development direction.
[0004] However, conventional chemical etching leveling faces a technical dilemma: to level the sharp microscopic protrusions on the copper foil surface, chemical dissolution with an etching solution is necessary. However, while dissolving the protrusions, the etching solution also indiscriminately dissolves the copper foil substrate and recessed areas, leading to a reduction in the overall thickness of the copper foil and a sharp decrease in mechanical properties (especially tensile strength). For ultra-thin copper foils of 9–35 μm, this overall thinning easily causes foil breakage and strip breakage, making continuous production impossible. Reducing the etching intensity to solve the thinning problem results in insufficient leveling effect and failure to meet surface roughness standards. This "roughness-strength" contradiction constitutes a long-standing unresolved technical bottleneck in this field. Existing technologies often only offer compromise solutions, failing to simultaneously achieve ultra-low roughness and excellent mechanical properties. Summary of the Invention
[0005] To address the problems in the prior art, the present invention aims to provide a method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards.
[0006] To achieve the above objectives and technical effects, the technical solution adopted by this invention is as follows: The production method of HVLP ultra-low profile copper foil for 6G communication and computing motherboards includes the steps of acid washing, water washing, roughening, curing, barrier layer electroplating, passivation and silane coupling modification of copper foil in sequence. After water washing and before roughening, a chemical polishing and leveling step is added. The chemical polishing and leveling step uses a low-corrosion polishing solution composed of sulfuric acid, hydroxycarboxylic acid complexing agent, nitrogen-containing heterocyclic corrosion inhibitor, and anionic surfactant to immerse and etch the rough surface of the copper foil. The nitrogen-containing heterocyclic corrosion inhibitor preferentially adsorbs onto the micro-recessed areas on the surface of the copper foil, inhibiting the etching of the recessed areas, thereby selectively dissolving sharp grain protrusions. While reducing the rough surface roughness Rz to below 0.5 μm, the copper foil thickness reduction rate does not exceed 5%. The immersion etching adopts a segmented gradient temperature control method, so that the copper foil first passes through a low-temperature pre-polishing zone of 25-35℃, and then passes through a high-temperature fine polishing zone of 45-55℃.
[0007] Furthermore, the mass percentage of each component in the low-corrosion polishing fluid is as follows: The composition consists of 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water.
[0008] Furthermore, the hydroxycarboxylic acid complexing agent is citric acid monohydrate, the nitrogen-containing heterocyclic corrosion inhibitor is 2-mercaptobenzimidazole, and the anionic surfactant is sodium dodecylbenzenesulfonate.
[0009] Furthermore, in the segmented gradient temperature control method, the temperature of the low-temperature pre-polishing zone is set to 28-35℃, the temperature of the high-temperature fine polishing zone is set to 46-55℃, the foil feeding speed is controlled at 2.5-10m / min, and the temperature of the low-temperature pre-polishing zone is matched with the foil feeding speed, so that the nitrogen-containing heterocyclic corrosion inhibitor is fully adsorbed during the residence time of the copper foil in the low-temperature pre-polishing zone to establish a selective etching mode.
[0010] Furthermore, in the chemical polishing and leveling step, the low-corrosion polishing solution is regenerated through online circulation filtration at a rate of 5-10 m. 3 A flow rate of / h continuously removes copper ions and solid impurities from the low-corrosion polishing solution, maintaining etching uniformity.
[0011] Furthermore, the thickness of the copper foil is 9–35 μm; when processing an extremely thin copper foil with a thickness of 9 μm, the concentration of the nitrogen-containing heterocyclic corrosion inhibitor in the low-corrosion polishing solution is increased to 1.2–1.5 wt%, and the temperature of the low-temperature pre-polishing zone is controlled below 28°C, the temperature of the high-temperature fine polishing zone is controlled below 50°C, and the foil feeding speed is reduced to below 4 m / min, in order to prevent the copper foil from thinning and breaking during the leveling process.
[0012] Furthermore, the roughening treatment involves electrodepositing a layer of copper particles on the flat, roughened surface after chemical polishing to form a roughened layer with a microscopic interlocking structure. The curing process involves electrodepositing a reinforced copper layer on the roughened layer to coat and anchor the copper particles. The barrier layer is electroplated as a nickel-zinc alloy layer with a thickness of 0.1 to 0.2 μm.
[0013] Furthermore, the pickling is performed by spraying or soaking with low-concentration dilute sulfuric acid; The resistivity of the pure water used for washing is not less than 18 MΩ·cm; The passivation is chromium-free passivation.
[0014] The present invention also discloses an HVLP ultra-low profile copper foil for 6G communication and computing motherboards, which is prepared by the production method of HVLP ultra-low profile copper foil for 6G communication and computing motherboards as described above. The surface roughness Rz of the HVLP ultra-low profile copper foil for 6G communication and computing motherboards is 0.32 to 0.48 μm, the peel strength after lamination with resin substrate is not less than 0.8 N / mm, and there is no delamination or blistering after 10 reflow soldering tests at 288℃.
[0015] This invention also discloses a low-corrosion polishing fluid, comprising the following components in weight percentages: The composition consists of 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) Solved the technical contradiction of "roughness-strength": Through the differential adsorption of corrosion inhibitors and the synergy of gradient temperature, the industrial-grade "selective leveling" was achieved for the first time, reducing Rz to below 0.5μm while the substrate was almost not thinned, overturning the technical prejudice of "leveling must be thinned" in the existing technology; 2) A non-obvious temperature control logic of "low temperature building mode and high temperature fine polishing" was proposed: the opposite effects of temperature on the adsorption of corrosion inhibitor and etching rate were combined in a time sequence to achieve a unity of selectivity and efficiency, which is the first of its kind in the field of copper foil chemical polishing. 3) A parameter linkage adjustment mechanism was established: the quantitative adjustment law between copper foil thickness and corrosion inhibitor concentration, temperature and speed was revealed, providing a scientific basis for the flexible production of the entire series of ultra-thin copper foils, rather than isolated process parameters; 4) Comprehensive performance has been significantly improved: the rough surface Rz of the finished copper foil can be stably maintained at 0.32~0.48μm, far exceeding that of imported similar products. At the same time, the peel strength is ≥0.8N / mm, and it has passed the rigorous test of 288℃ and 10 reflow soldering cycles, fully meeting the extreme application requirements of 6G and AI computing power. Attached Figure Description
[0017] Figure 1 This is an electron microscope image of Embodiment 1 of the present invention; Figure 2 This is an electron microscope image of Comparative Example 1 of the present invention. Detailed Implementation
[0018] The present invention will now be described in detail so that its advantages and features can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.
[0019] The following provides a brief overview of one or more aspects to offer a basic understanding of them. This overview is not an exhaustive summary of all conceived aspects, nor is it intended to identify key or decisive elements of all aspects, nor to define the scope of any or all aspects. Its sole purpose is to present some concepts of one or more aspects in a simplified form to prepare for the more detailed descriptions that follow.
[0020] like Figure 1 As shown, this invention discloses a method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards. The method includes sequentially performing acid washing, water washing, roughening, curing, barrier layer electroplating, passivation, and silane coupling modification on the copper foil. After water washing and before roughening, a chemical polishing and leveling step is added. This chemical polishing and leveling step uses a low-corrosion polishing solution composed of sulfuric acid, a hydroxycarboxylic acid complexing agent, a nitrogen-containing heterocyclic corrosion inhibitor, and an anionic surfactant to immerse and etch the rough surface of the copper foil. The nitrogen-containing heterocyclic corrosion inhibitor, due to the thiol groups and nitrogen-containing heterocycles in its molecular structure, can preferentially and strongly adsorb onto the microscopic depressions on the copper foil surface, inhibiting etching of these depressions. This allows the low-corrosion polishing solution to selectively dissolve sharp grain protrusions, reducing the surface roughness Rz to below 0.5 μm while ensuring that the copper foil thickness reduction rate does not exceed 5%, with almost no degradation in mechanical properties.
[0021] In some implementations, the immersion etching employs a segmented gradient temperature control method, whereby the copper foil first passes through a low-temperature pre-polishing zone of 25–35°C, where the nitrogen-containing heterocyclic corrosion inhibitor is fully adsorbed and a selective etching mode is established; then it passes through a high-temperature fine polishing zone of 45–55°C, where the protrusions are dissolved more quickly while maintaining selectivity, thus completing the precision leveling.
[0022] In some specific implementations, in the segmented gradient temperature control method, the temperature of the low-temperature pre-polishing zone is set to 28-35°C, the temperature of the high-temperature fine polishing zone is set to 46-55°C, the foil feeding speed is controlled at 2.5-10 m / min, and the temperature of the low-temperature pre-polishing zone is matched with the foil feeding speed, so that the nitrogen-containing heterocyclic corrosion inhibitor is fully adsorbed during the residence time of the copper foil in the low-temperature pre-polishing zone to establish a selective etching mode.
[0023] In some embodiments, the mass percentage of each component in the low-corrosion polishing fluid is as follows: The composition comprises 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water. The preferred hydroxycarboxylic acid complexing agent is citric acid monohydrate, the preferred nitrogen-containing heterocyclic corrosion inhibitor is 2-mercaptobenzimidazole, and the preferred anionic surfactant is sodium dodecylbenzenesulfonate. The components of this formulation work synergistically: sulfuric acid provides basic etching capability; citric acid monohydrate complexes dissolved copper ions, promoting the reaction forward and preventing precipitation; 2-mercaptobenzimidazole plays a key selective inhibitory role; and sodium dodecylbenzenesulfonate reduces surface tension, allowing the polishing solution to spread evenly on the microscopic surface and eliminating uneven polishing in certain areas.
[0024] In some embodiments, during the chemical polishing and leveling step, the low-corrosion polishing solution is regenerated through online circulation filtration at a rate of 5–10 m. 3 A flow rate of / h continuously removes copper ions and solid impurities from the low-corrosion polishing solution, maintaining etching uniformity.
[0025] This invention possesses exceptional thickness adaptability, particularly suitable for ultra-thin copper foils ranging from 9 to 35 μm. The inventors discovered a synergistic adjustment mechanism: the thinner the copper foil, the greater the need for enhanced selective protection and reduced etching intensity. When processing ultra-thin copper foils of 9 μm thickness, the concentration of nitrogen-containing heterocyclic corrosion inhibitors in the low-corrosion polishing solution is increased to 1.2–1.5 wt%, while the temperature of the low-temperature pre-polishing zone is controlled below 28°C, the temperature of the high-temperature fine polishing zone is controlled below 50°C, and the foil feeding speed is reduced to below 4 m / min. This synergistic adjustment of "increasing corrosion inhibition / reducing temperature / slowing down speed" ensures that the ultra-thin copper foil does not experience over-etching or band breakage during leveling, allowing for predictable application to different thickness specifications without the need for repeated trial and error.
[0026] In some implementations, the roughening process involves electrodepositing a layer of copper particles onto a flat, roughened surface after chemical polishing, forming a roughened layer with a microscopic interlocking structure.
[0027] In some implementations, the curing process involves electrodepositing a reinforcing copper layer on the roughened layer to coat and anchor the copper particles.
[0028] In some embodiments, the barrier layer is electroplated as a nickel-zinc alloy layer with a thickness of 0.1 to 0.2 μm.
[0029] In some implementations, pickling is performed by spraying or soaking with a low concentration of dilute sulfuric acid.
[0030] In some implementations, the resistivity of the pure water used for washing is not less than 18 MΩ·cm.
[0031] In some implementations, passivation is performed as chromium-free passivation.
[0032] After chemical polishing, the copper foil possesses a flat substrate with an ultra-low profile. Subsequent roughening and curing electrodeposit fine and uniform copper particles on this substrate, enabling the construction of a reliable mechanical interlocking structure without increasing roughness, thus solving the inherent problem of insufficient peel strength in ultra-low profile copper foil. The subsequent electroplating of a nickel-zinc alloy barrier layer, a chromium-free passivation layer, and a silane coupling modification layer further endow the copper foil with excellent heat resistance, oxidation resistance, and resin interfacial adhesion.
[0033] This invention also discloses an HVLP ultra-low profile copper foil for 6G communication and computing motherboards. It is prepared using the aforementioned production method for HVLP ultra-low profile copper foil for 6G communication and computing motherboards. Its surface roughness Rz is 0.32–0.48 μm, and its peel strength after lamination with a resin substrate is not less than 0.8 N / mm. Furthermore, it shows no delamination or blistering after 10 reflow soldering cycles at 288°C. It is suitable for high-frequency, high-speed printed circuit boards such as those used in 6G millimeter-wave communication and AI high-computing servers.
[0034] This invention also discloses a low-corrosion polishing fluid, comprising the following components in weight percentages: The composition consists of 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water.
[0035] The core concept of this invention lies in transforming "indiscriminate full-surface etching" into "selective protrusion etching." Through research, the inventors discovered that by utilizing the differentiated adsorption behavior of specific corrosion inhibitors in the microscopic uneven regions of a copper surface, a "chemical scissors" can be constructed. Corrosion inhibitor molecules preferentially and densely adsorb at microscopic depressions and grain boundary trenches with lower surface energy, forming a molecular-level protective film that inhibits etching in these areas. Meanwhile, at the tips of microscopic sharp protrusions, where charge density and surface energy are high, the corrosion inhibitor adsorption layer is relatively loose and preferentially dissolved in the etching solution. This achieves the ideal leveling effect of "only removing peaks, not filling valleys, and not damaging the substrate."
[0036] Building upon this, the inventors further discovered that temperature has a non-linear regulatory effect on the aforementioned selective etching process. At relatively low temperatures (25–35°C), the etchant adsorbs more abundantly on the copper surface, resulting in a denser adsorption film and extremely high selectivity. This allows for the precise removal of the most prominent whiskers and sharp corners, creating a smooth substrate. Subsequently, raising the temperature to 45–55°C accelerates the reaction rate, efficiently smoothing out the remaining lower-height protrusions. At this point, the smoothed area remains effectively protected by the etchant. This gradient temperature control logic of "high selectivity at low temperatures and high-efficiency polishing at high temperatures" avoids the indiscriminate and severe corrosion in the initial stage of the reaction under high temperatures alone, while overcoming the low smoothing efficiency under low temperatures alone. This allows for the unification of selective etching and large-scale continuous production.
[0037] Example 1
[0038] Take an initial copper foil with a thickness of 9μm and process it according to the following procedure: Pickling: 3% dilute sulfuric acid, sprayed at room temperature, foil feeding speed 4m / min.
[0039] Pre-wash: 3-stage 18.2MΩ·cm ultrapure water countercurrent rinsing.
[0040] Chemical polishing: A low-corrosion polishing solution is used, formulated with 30% sulfuric acid, 1.2% citric acid monohydrate, 0.8% 2-mercaptobenzimidazole, 0.05% sodium dodecylbenzenesulfonate, and the balance ultrapure water. The pre-polishing zone is 30℃, the fine polishing zone is 50℃, the foil feeding speed is 4m / min, and simultaneous online circulating filtration (flow rate 5m³ / min) is implemented. 3 / h).
[0041] Post-wash: 4-stage counter-current pure water wash.
[0042] Coarsening: 1.5A / dm 2 Curing: 2.0 A / dm 2 .
[0043] Nickel-zinc alloy electroplating: 0.1μm.
[0044] Chromium-free passivation.
[0045] Silane coupling agent coating, dried at 90℃ and wound up.
[0046] Finished product inspection: Rz = 0.32μm (e.g.) Figure 1 The copper foil thickness was reduced by 3.2%, and the tensile strength decreased by only 2% compared with the initial copper foil; the peel strength was 0.80 N / mm, and there was no delamination or blistering after 10 reflow solderings at 288℃.
[0047] Example 2
[0048] Take a 15μm thick initial copper foil and process it according to the following procedure: Pickling: 4% dilute sulfuric acid, sprayed at room temperature, foil feeding speed 5m / min.
[0049] Pre-wash: 3-stage 18.2MΩ·cm ultrapure water countercurrent rinsing.
[0050] Chemical polishing: A low-corrosion polishing solution is used, formulated with 30% sulfuric acid, 1.2% citric acid monohydrate, 1.0% 2-mercaptobenzimidazole, 0.05% sodium dodecylbenzenesulfonate, and the balance ultrapure water. The pre-polishing zone is 32℃, the fine polishing zone is 52℃, the foil feeding speed is 3.5m / min, and simultaneous online circulating filtration (flow rate 6m³ / min) is implemented. 3 / h).
[0051] Post-wash: 4-stage counter-current pure water wash.
[0052] Coarsening: 2.0A / dm 2 Curing: 2.0 A / dm 2 .
[0053] Nickel-zinc alloy electroplating: 0.15μm.
[0054] Chromium-free passivation.
[0055] Silane coupling agent coating, dried at 100℃ and wound up.
[0056] Finished product inspection: Rz=0.38μm, thickness reduction rate 2.8%, peel strength 0.82N / mm, no delamination or blistering after 10 reflow soldering cycles.
[0057] Example 3
[0058] Take an initial copper foil with a thickness of 35μm and process it according to the following procedure: Pickling: 2.5% dilute sulfuric acid, sprayed at room temperature, foil feeding speed 2.5m / min.
[0059] Pre-wash: 3-stage 18.2MΩ·cm ultrapure water countercurrent rinsing.
[0060] Chemical polishing: A low-corrosion polishing solution is used, formulated with 30% sulfuric acid, 1.2% citric acid monohydrate, 1.2% 2-mercaptobenzimidazole, 0.05% sodium dodecylbenzenesulfonate, and the balance ultrapure water. The pre-polishing zone is 28℃, the fine polishing zone is 46℃, the foil feeding speed is 2.5m / min, and simultaneous online circulating filtration (flow rate 7m³ / min) is implemented. 3 / h).
[0061] Post-wash: 4-stage counter-current pure water wash.
[0062] Coarsening: 2.5A / dm 2 Curing: 3.0 A / dm 2 .
[0063] Nickel-zinc alloy electroplating: 0.15μm.
[0064] Chromium-free passivation.
[0065] Silane coupling agent coating, dried at 100℃ and wound up.
[0066] Finished product inspection: Rz=0.48μm, thickness reduction rate 2.1%, peel strength 0.96N / mm, no delamination or blistering after 10 reflow soldering cycles.
[0067] Comparative Example 1 The difference between this comparative example and Example 1 is that this comparative example completely eliminates the pre-washing, chemical polishing and post-washing steps, and directly performs subsequent treatments such as roughening after acid washing.
[0068] Finished product inspection: Rz = 3.2μm (e.g., surface roughness). Figure 2 The peel strength was 0.76 N / mm, and severe delamination and blistering occurred after 10 reflow soldering cycles at 288℃. Comparative results show that the absence of the chemical polishing and leveling process described in this invention results in a roughness nearly an order of magnitude higher and poorer thermal reliability.
[0069] Comparative Example 2 The difference between this comparative example and Example 2 is that this comparative example does not include a chemical polishing step.
[0070] Finished product inspection: Rz=5.2μm, delamination and bubbling after reflow soldering.
[0071] Comparative Example 3 The difference between this comparative example and Example 3 is that this comparative example does not include a chemical polishing step.
[0072] Finished product inspection: Rz=7.5μm, delamination and bubbling after reflow soldering.
[0073] The comparative results show that the core of this invention—pre-process segmented gradient temperature-controlled chemical polishing—is the decisive factor in achieving an order-of-magnitude reduction in roughness without damaging mechanical properties. Subsequent roughening, blocking, and passivation processes alone cannot completely change the inherently high roughness of the original foil. Furthermore, Example 3, by increasing the corrosion inhibitor concentration and lowering the temperature, ensured that the thick copper foil could still achieve the target roughness at a lower etching intensity, with an even lower thinning rate, verifying the discovered parameter linkage mechanism.
[0074] Any parts or structures not specifically described in this invention can be made using existing technologies or products, and will not be elaborated upon here.
[0075] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
A method for producing HVLP ultra-low profile copper foil for 1.6G communication and computing motherboards, characterized in that, The process includes sequential steps of pickling, washing, roughening, curing, barrier layer electroplating, passivation, and silane coupling modification of copper foil. A chemical polishing and leveling step is added after washing and before roughening. The chemical polishing and leveling step uses a low-corrosion polishing solution composed of sulfuric acid, hydroxycarboxylic acid complexing agent, nitrogen-containing heterocyclic corrosion inhibitor, and anionic surfactant to immerse and etch the rough surface of the copper foil. The nitrogen-containing heterocyclic corrosion inhibitor preferentially adsorbs onto the micro-recessed areas on the surface of the copper foil, inhibiting the etching of the recessed areas, thereby selectively dissolving sharp grain protrusions. While reducing the rough surface roughness Rz to below 0.5 μm, the copper foil thickness reduction rate does not exceed 5%. The immersion etching adopts a segmented gradient temperature control method, so that the copper foil first passes through a low-temperature pre-polishing zone of 25-35℃, and then passes through a high-temperature fine polishing zone of 45-55℃.
2. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, The mass percentage of each component in the low-corrosion polishing fluid is as follows: The composition consists of 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water.
3. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 2, characterized in that, The hydroxycarboxylic acid complexing agent is citric acid monohydrate, the nitrogen-containing heterocyclic corrosion inhibitor is 2-mercaptobenzimidazole, and the anionic surfactant is sodium dodecylbenzenesulfonate.
4. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, In the segmented gradient temperature control method, the temperature of the low-temperature pre-polishing zone is set to 28-35℃, the temperature of the high-temperature fine polishing zone is set to 46-55℃, and the foil feeding speed is controlled at 2.5-10m / min. The temperature of the low-temperature pre-polishing zone is matched with the foil feeding speed, so that the nitrogen-containing heterocyclic corrosion inhibitor is fully adsorbed during the residence time of the copper foil in the low-temperature pre-polishing zone to establish a selective etching mode.
5. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, In the chemical polishing and leveling step, the low-corrosion polishing solution is regenerated through online circulation filtration at a rate of 5-10m. 3 A flow rate of / h continuously removes copper ions and solid impurities from the low-corrosion polishing solution, maintaining etching uniformity.
6. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, The thickness of the copper foil is 9–35 μm. When processing an extremely thin copper foil with a thickness of 9 μm, the concentration of nitrogen-containing heterocyclic corrosion inhibitor in the low-corrosion polishing solution is increased to 1.2–1.5 wt%, and the temperature of the low-temperature pre-polishing zone is controlled below 28°C, the temperature of the high-temperature fine polishing zone is controlled below 50°C, and the foil feeding speed is reduced to below 4 m / min to prevent the copper foil from thinning and breaking during the leveling process.
7. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, The roughening process involves electrodepositing a layer of copper particles onto the flat, roughened surface after chemical polishing to form a roughened layer with a micro-interlocking structure. The curing process involves electrodepositing a reinforced copper layer on the roughened layer to coat and anchor the copper particles. The barrier layer is electroplated as a nickel-zinc alloy layer with a thickness of 0.1 to 0.2 μm.
8. The method for producing HVLP ultra-low profile copper foil for 6G communication and computing motherboards according to claim 1, characterized in that, The pickling is performed by spraying or soaking with low-concentration dilute sulfuric acid. The resistivity of the pure water used for washing is not less than 18 MΩ·cm; The passivation is chromium-free passivation. 9.6G communication and computing motherboard using HVLP ultra-low profile copper foil, characterized in that, The HVLP ultra-low profile copper foil for 6G communication and computing motherboards is prepared using the production method described in claims 1-8. The surface roughness Rz of the HVLP ultra-low profile copper foil for 6G communication and computing motherboards is 0.32-0.48 μm, the peel strength after being pressed with the resin substrate is not less than 0.8 N / mm, and there is no delamination or blistering after 10 reflow soldering tests at 288℃.
10. A low-corrosion polishing fluid, characterized in that, The components include the following components in percentage by mass: The composition consists of 25–35 wt% sulfuric acid, 0.8–2.0 wt% hydroxycarboxylic acid complexing agent, 0.5–1.5 wt% nitrogen-containing heterocyclic corrosion inhibitor, 0.03–0.08 wt% anionic surfactant, and the balance being ultrapure water.